SEJARAH PENDIDIKAN ISLAM DI KERJAAN TURKI USMANI - Ahmad Badwi (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2018)
Islamic Education in the Ottoman Empire, the sciences of Naqliyah did not make much progress because the door of ijtihad was closed, the education was aimed at supporting certain schools of thought. The educational activities of this period were influenced by Sufi teachings. The education system is memorized so that reasoning is less developed. At the end of the reign of education renewed by following the western method. While Islamic education in the Safavid period in Persia developed a lot of reasoning that gave birth to the Philsofot, but the goal of education was directed to develop a twelve Shiite flow. While Islamic education in the Mughal empire in India is intended to support the interests of the authorities and clean up the teachings that are not from Islam, education activities are not only nnaqliyah science but also history and literature. Islamic education in this period is also influenced by Sufi teachings.